2020
DOI: 10.21037/atm-20-5556
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HULC shRNA disinhibits miR-377-5p to suppress the growth and invasion of hepatocellular carcinoma in vitro and hepatocarcinogenesis in vivo

Abstract: Background: Aberrant expression of up-regulated long non-coding RNA [LncRNA highly upregulated in liver cancer (HULC)] has been observed to play an important regulatory role in the development of multiple human diseases. However, the molecular mechanism underlying the role of HULC and miR-377-5p in HCC needs to be urgently explored. Methods:The mRNA and protein expression levels of HULC were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot in hepatocellular carcinoma (HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…It is noteworthy that most experiments have focused on revealing the role of tumor-promoting factors. It has been shown that siRNA and shRNA can be applied to down-regulate lncRNAs [ 410 , 411 ]. Thus, next experiments can focus on the targeting of ncRNAs and translating these findings in clinical settings.…”
Section: Biomarker Applicationmentioning
confidence: 99%
“…It is noteworthy that most experiments have focused on revealing the role of tumor-promoting factors. It has been shown that siRNA and shRNA can be applied to down-regulate lncRNAs [ 410 , 411 ]. Thus, next experiments can focus on the targeting of ncRNAs and translating these findings in clinical settings.…”
Section: Biomarker Applicationmentioning
confidence: 99%
“…HULC knockdown increased the chemosensitivity to oxaliplatin through the repression of cell growth and the acceleration apoptosis in HCC cells. Further analysis confirmed its mode of action through the regulation of the miR-383-5p/vesicle-associated membrane protein-2 axis, the miR-377-5p/HIF-1α pathway, and the miR-134-5p/FOXM1 axis [41,42]. Emerging evidence provides new insights on the role of other lncRNAs in HCC development, such as NEAT1, ANRIL, SNHG1, or H19 [36,69].…”
Section: Non-coding Rnasmentioning
confidence: 79%
“…Regulation of mitochondrial metabolism [38] HULC Growth of liver cancer stem cells [39] Chemosensitivity of anti-cancer drug oxaliplatin inhibition [40] Regulation of miR-383-5p/vesicle-associated membrane protein-2 pathway; miR-377-5p/HIF-1α pathway and miR-134-5p/FOXM1 pathway [41,42] On the contrary, hypermethylation may disturb the function of another group of genes. One of the signaling pathways affected by hypermethylation is the WNT/β-catenin signaling.…”
Section: Malat1mentioning
confidence: 99%
“…Moreover, miR-377-5p overexpression aggrandized myocardial dysfunction as well as apoptosis, and promoted the release of inflammatory factors [ 81 ]. However, miR-377-5p downregulation suppressed the proliferation and invasion of HepG2 cells belonging to hepatocellular carcinoma cell lines [ 82 ]. Interestingly, Li Y, et al [ 83 ] has demonstrated that miR-377-5p was up-regulated after propofol treatment and contributed to induce neurotoxicity, the result was consistent with our finding.…”
Section: Discussionmentioning
confidence: 99%